A transition metal oxide / carbon composite microsphere and its preparation method and application

By preparing transition metal oxide/carbon composite microspheres, the problems of low specific surface area utilization and complex synthesis steps of carbon-based materials are solved, achieving efficient energy storage and simplified processes under low specific surface area, with high specific capacitance and long cycle Advantages of longevity.

CN118629789BActive Publication Date: 2025-01-21HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410805624.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-01-21
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The carbon-based materials used in the prior art for supercapacitor electrode materials have problems such as low specific surface area utilization and complex synthesis steps.

Method used

Transition metal oxide/carbon composite microspheres are used to prepare the microsphere precursor through the reaction of golf ball-like polymer microspheres and inorganic salts containing transition metals in an alcoholic aqueous solution, followed by high-temperature carbonization and oxidation under argon protection to form a surface Carbon microspheres with uniformly distributed transition metal oxide particles.

Benefits of technology

It achieves efficient energy storage under low specific surface area, simplifies the synthesis process, avoids the cumbersome steps of pore creation by template method or activation method, and the material has high specific capacitance and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118629789B_ABST
    Figure CN118629789B_ABST
Patent Text Reader

Abstract

The present invention relates to a transition metal oxide / carbon composite microsphere and a preparation method and application thereof, and relates to the technical field of composite material technology. The present invention solves the technical problems of low specific surface area utilization and complicated synthesis steps of carbon-based materials used for supercapacitor electrode materials in the prior art. The present invention prepares precursor microspheres by adsorption reaction of a golf ball-like polymer microsphere substrate and an inorganic salt containing a transition metal, and prepares the transition metal oxide / carbon composite microspheres by a one-step pyrolysis and carbonization method. The method of the present invention can eliminate the cumbersome steps of pore formation by a template method or an activation method to achieve one-step pore formation, and the obtained transition metal oxide / carbon composite microsphere material has the advantages of high specific capacitance, long cycle life, and simple carbonization step, and realizes efficient energy storage under low specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a transition metal oxide / carbon composite microsphere and a preparation method and application thereof. Background Art

[0002] With the development of science and technology and the increase in energy demand, new energy storage devices have attracted much attention worldwide. Among them, supercapacitors, as a new type of energy storage device, have gradually become a research hotspot in the field of energy storage due to their advantages such as high power density, fast charging and discharging, long life cycle, and environmental friendliness. They have provided new technical support for energy, transportation, industry and other fields, helping to reduce energy waste, mitigate environmental pollution, and promote the optimization of my country's energy structure.

[0003] Supercapacitors are mainly composed of three parts: electrodes, electrolytes, and diaphragms. The electrolyte is the medium for transferring ions between electrodes, which affects the electrochemical properties of supercapacitors; the diaphragm isolates the electrodes and prevents short circuits; the electrode is the core part of the supercapacitor, responsible for storing and transmitting electrical energy. The most widely studied electrode materials currently include carbon materials, metal oxides, and conductive polymers. Among them, carbon material electrodes have been widely studied due to their high chemical stability, corrosion resistance, good electrical conductivity, and large specific surface area. However, their specific capacity is always low, which limits their further application.

[0004] In order to improve the energy storage performance of carbon materials, the methods of designing porous structures and compounding with metal oxides are currently mainly used. For example, Jing Gao et al. published a paper titled "Biomass-based controllable morphology of carbon microspheres with multi-layer hollow structure for superior performance in supercapacitors" that used hexadecyltrimethylammonium bromide (CTAB) as a soft template to form corn starch (CS)-based carbon microspheres with radial hollow structures in the inner and middle layers through hydrothermal and sol-gel methods. The maximum specific surface area of ​​the material is 1572.93 m 2 / g, the highest specific capacitance is 242.5F / g (Journal of Colloid and Interface Science, 658 (2024): 90-99.). Haotong Li et al. disclosed a manganese tetraoxide / biomass porous carbon material in a paper titled "Amanganese oxide / biomass porous carbon composite for high-performance supercapacitor electrodes", which has a high specific capacitance of 482F / g (Electrochimica Acta 473 (2024) 143514).

[0005] The carbon-based materials prepared by the above-mentioned preparation methods have good energy storage performance when used to make supercapacitor electrode materials. However, in practical applications, the large specific surface area cannot be fully utilized, resulting in low actual capacity. At the same time, the construction of porous structures requires the use of soft templates or chemical activation, and the processing steps are complicated and difficult to industrialize. Therefore, it is particularly important to achieve efficient energy storage of carbon-based electrode materials with low specific surface areas through simple synthesis processes. Summary of the invention

[0006] The present invention aims to solve the technical problems of low specific surface area utilization and complicated synthesis steps of carbon-based materials used as supercapacitor electrode materials in the prior art, and provides a transition metal oxide / carbon composite microsphere and a preparation method and application thereof.

[0007] In order to solve the above technical problems, the technical solutions of the present invention are as follows:

[0008] A transition metal oxide / carbon composite microsphere, which uses a carbon microsphere as a carrier, and the surface of the carbon microsphere is concave and evenly distributed with one or more transition metal oxide particles;

[0009] The carbon microspheres are formed by carbonizing golf ball-shaped polymer microspheres and have wrinkles on the surface;

[0010] The transition metal oxide particles are formed by adsorbing inorganic salts containing transition metals on the surface of golf ball-like polymer microspheres and then carbonizing and oxidizing them at high temperature.

[0011] In the above technical solution, preferably, the transition metal oxide / carbon composite microspheres contain three elements of C, N, and O, and at least one of four elements of Mn, Co, Fe, and Ni.

[0012] In the above technical solution, preferably, the carbon microspheres have a particle size of 2 to 6 μm and a specific surface area of ​​208 to 252 m 2 ·g-1 , the average pore diameter is 2.1824~2.2453nm.

[0013] In the above technical scheme, preferably, the golf ball-like polymer microspheres are selected from poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl phthalate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl phthalate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl isophthalate-co-cyclohexyl methacrylate-co-acrylonitrile) or poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile).

[0014] In the above technical scheme, it is further preferred that the golf ball-like polymer microspheres are selected from poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres or poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile).

[0015] In the above technical scheme, preferably, the inorganic salt containing a transition metal is selected from potassium permanganate, manganese chloride, manganese chloride tetrahydrate, manganese sulfate, cobalt chloride, cobalt chloride hexahydrate, cobalt sulfate, ferric chloride, ferric chloride hexahydrate, ferric sulfate, iron (II) chloride hydrate, nickel chloride, nickel chloride hexahydrate or nickel sulfate.

[0016] In the above technical scheme, it is further preferred that the inorganic salt containing a transition metal is characterized in that it is selected from potassium permanganate, cobalt chloride, manganese chloride tetrahydrate, cobalt chloride hexahydrate, ferric chloride hexahydrate, nickel chloride hexahydrate, manganese sulfate, cobalt sulfate, ferric sulfate or nickel sulfate.

[0017] A method for preparing transition metal oxide / carbon composite microspheres comprises the following steps:

[0018] A. Preparation of microsphere precursor

[0019] Putting golf ball-shaped polymer microspheres and one or more inorganic salts containing transition metals into an alcohol aqueous solution with a concentration of 20 to 80% by weight, dissolving and dispersing by ultrasonication to obtain a mixed solution I;

[0020] The mass ratio of the inorganic salt containing transition metal, golf ball-shaped polymer microspheres and alcohol aqueous solution is 0.002-0.02:0.008-0.08:1;

[0021] The mixed solution I was transferred to a three-necked flask, and reacted for 1-5 hours at room temperature and a stirring speed of 300-800 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor;

[0022] B. Preparation of transition metal oxide / carbon composite microspheres

[0023] The microsphere precursor obtained in step A is placed in a tubular furnace, heated to 600-1000° C. at a gas flow rate of 100-200 mL / min and a heating rate of 2.0-10.0° C. / min under argon protection, and carbonized for 1-4 hours to obtain a black product, which is the transition metal oxide / carbon composite microsphere.

[0024] In the above technical solution, preferably, the alcohol aqueous solution is methanol aqueous solution, ethanol aqueous solution, isopropanol aqueous solution, n-propanol aqueous solution or tert-butanol aqueous solution.

[0025] The invention discloses an application of transition metal oxide / carbon composite microspheres in preparing supercapacitor electrode materials.

[0026] The beneficial effects of the present invention are:

[0027] The transition metal oxide / carbon composite microspheres of the present invention are prepared by adsorbing a golf ball-shaped polymer microsphere substrate synthesized independently and an inorganic salt containing a transition metal to prepare a precursor microsphere, and then preparing the transition metal oxide / carbon composite microspheres by a one-step pyrolysis and carbonization method. The method of the present invention can achieve one-step pore formation by eliminating the cumbersome steps of pore formation by the template method or activation method. At the same time, the present invention adjusts the pore structure and element composition of the carbon microspheres by controlling the type and adsorption amount of the inorganic salt containing the transition metal, thereby changing the specific surface area and stability of the carbon microspheres to obtain high-performance supercapacitor electrode materials. The transition metal oxide / carbon composite microspheres are in a 4-6 mol / L KOH electrolyte and a current density of 0.5-10A·g -1 The mass specific capacitance is 387~214F·g -1 When the current density is 10A·g -1 The capacitance retention rate after 10,000 charge and discharge cycles is 96%. Compared with the porous carbon microsphere materials reported so far, this transition metal oxide / carbon composite microsphere material does not require activation and pore formation, has the advantages of high specific capacitance, long cycle life, and simple carbonization steps, achieving efficient energy storage under low specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 3 is a structural characterization diagram of the transition metal oxide / carbon composite microspheres prepared in Example 1, wherein a is a scanning electron microscope diagram, b is a nitrogen adsorption-desorption curve diagram, and c is an X-ray diffraction diagram.

[0029] Figure 2 This is a scanning electron microscope image of the transition metal oxide / carbon composite microspheres prepared in Example 2.

[0030] Figure 3 This is a scanning electron microscope image of the transition metal oxide / carbon composite microspheres prepared in Example 3.

[0031] Figure 4 This is a scanning electron microscope image of the transition metal oxide / carbon composite microspheres prepared in Example 4.

[0032] Figure 5 This is a scanning electron microscope image of the transition metal oxide / carbon composite microspheres prepared in Example 5.

[0033] Figure 6 The transition metal oxide / carbon composite microspheres prepared in Example 1 are used as electrode performance characterization diagrams, wherein a is a cyclic voltammogram, b is a constant current charge and discharge diagram, and c is an electrochemical impedance diagram. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0035] The present invention provides a transition metal oxide / carbon composite microsphere, which is a composite material with carbon microspheres as carriers, and the surface of the carbon microspheres is concave and uniformly distributed with different transition metal oxide particles. The carbon microspheres are carbonized from golf ball-like polymer microspheres, have wrinkles on the surface, contain three elements of C, N, and O, and contain at least one of four elements of Mn, Co, Fe, and Ni. The particle size of the carbon microspheres is 2 to 6 μm, and the specific surface area is 208 to 252 m 2 ·g -1 The average pore diameter is 2.1824-2.2453 nm. The transition metal oxide particles are formed by adsorbing inorganic salts containing transition metals on the surface of golf ball-like polymer microspheres and then carbonizing and oxidizing them at high temperature. The transition metal is selected from at least one of Mn, Co, Fe and Ni.

[0036] In the present invention, the golf ball-like polymer microspheres play the role of providing C, N, and O elements and providing attachment sites for transition metal oxide particles in the process of preparing transition metal oxide / carbon composite microspheres.

[0037] The golf ball-like polymer microspheres are preferably selected from poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl phthalate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl isophthalate-co-cyclohexyl methacrylate-co-acrylonitrile) or poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile). It is further preferred that the golf ball-like polymer microspheres are selected from poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres or poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile). These golf ball-like polymer microspheres used in the present invention are prepared according to the preparation method described in CN 117577453 A, the invention titled "A golf ball-like porous carbon material and its preparation method and application"; the golf ball-like polymer microspheres used in the following examples are prepared with reference to the examples of CN117577453 A.

[0038] In the present invention, the inorganic salt containing transition metal plays a role in adjusting the product morphology, stabilizing the morphology of carbon microspheres, introducing transition metals to form transition metal oxides, and increasing pseudocapacitance during the preparation of transition metal oxide / carbon composite microspheres.

[0039] The inorganic salt containing transition metal is preferably selected from potassium permanganate, manganese chloride, manganese chloride tetrahydrate, manganese sulfate, cobalt chloride, cobalt chloride hexahydrate, cobalt sulfate, ferric chloride, ferric chloride hexahydrate, ferrous sulfate or ferrous chloride (II) hydrate, nickel chloride, nickel chloride hexahydrate or nickel sulfate. Further preferably, the inorganic salt containing transition metal is characterized in that it is selected from potassium permanganate, cobalt chloride, manganese chloride tetrahydrate, cobalt chloride hexahydrate, ferric chloride hexahydrate, nickel chloride hexahydrate, manganese sulfate, cobalt sulfate, ferric sulfate or nickel sulfate. The inorganic salt containing transition metal used in the present invention is all products currently sold on the market, such as potassium permanganate sold by Sinopharm Chemical Reagent Co., Ltd. under the trade name potassium permanganate.

[0040] The present invention also provides a method for preparing transition metal oxide / carbon composite microspheres, and the preparation steps of the preparation method are as follows:

[0041] A. Preparation of microsphere precursor

[0042] Putting golf ball-shaped polymer microspheres and inorganic salts containing transition metals into an alcohol aqueous solution with a concentration of 20 to 80% by weight, dissolving and dispersing by ultrasonication to obtain a mixed solution I;

[0043] The mass ratio of the inorganic compound containing transition metal, golf ball-shaped polymer microspheres and alcohol aqueous solution is 0.002-0.02:0.008-0.08:1;

[0044] The mixed solution I was transferred to a three-necked flask, and reacted for 1-5 hours at room temperature and a stirring speed of 300-800 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor.

[0045] In the present invention, the alcohol aqueous solution serves as a solvent medium for the smooth adsorption reaction of the inorganic salt containing the transition metal and the golf ball-like polymer microspheres during the preparation of the transition metal oxide / carbon composite microspheres.

[0046] The alcohol aqueous solution is an aqueous solution of methanol, ethanol, isopropanol, n-propanol or tert-butanol, and the methanol, ethanol, isopropanol, n-propanol or tert-butanol used in the present invention are all products currently sold on the market, such as ethanol sold by Sinopharm Chemical Reagent Co., Ltd. under the trade name of ethanol.

[0047] The concentration of the alcohol aqueous solution used in the present invention is 20-80% by weight. If the concentration of the alcohol aqueous solution is lower than 20%, the golf ball-shaped polymer microspheres cannot be well dispersed and adsorbed with inorganic salts; if the concentration of the alcohol aqueous solution is higher than 80%, the inorganic salts cannot be quickly dissolved and the solubility is not high, and the transition metal oxide / carbon composite microspheres cannot be prepared. Therefore, the concentration of the alcohol aqueous solution is appropriately 20-80%, preferably 40-60%.

[0048] According to the present invention, when the amount of the inorganic salt containing transition metal and the alcohol aqueous solution is within the above range, if the amount of the golf ball-shaped polymer microspheres is less than 0.008 or greater than 0.08, the morphology and structure of the transition metal oxide / carbon composite microspheres prepared subsequently are greatly different from the target, so that the transition metal oxide / carbon composite microspheres with stable morphology cannot be obtained, which seriously affects the energy storage performance as a supercapacitor electrode. Therefore, the amount of the golf ball-shaped polymer microspheres is appropriately 0.008-0.08, preferably 0.01-0.05.

[0049] According to the present invention, when the amount of golf ball-like polymer microspheres and alcohol aqueous solution is within the range, if the amount of inorganic salt containing transition metal is less than 0.002, the oxide is too little distributed on the surface of golf ball-like polymer microspheres, and cannot provide support to maintain the spherical structure of carbon microspheres during carbonization; if the content of inorganic salt containing transition metal is higher than 0.02, more oxide particles will be present on the surface of carbon microspheres, resulting in blockage of pores on the surface of carbon microspheres, reducing energy storage efficiency. Therefore, it is reasonable to use an inorganic salt containing transition metal in an amount of 0.002-0.02, preferably 0.005-0.01.

[0050] In this step, when the reaction temperature and reaction time are within the range, if the stirring speed is lower than 300 rpm, the transition metal oxide particles on the surface of the transition metal oxide / carbon composite microspheres obtained by the adsorption of inorganic salts on the golf ball-like polymer microspheres are unevenly distributed; if the stirring speed is higher than 800 rpm, the amount of inorganic salts adsorbed by the polymer microspheres is not high, and the amount of transition metal oxide particles formed on the surface of the carbon microspheres is low. Therefore, the stirring speed is appropriately 300-800 rpm, preferably 300-500 rpm.

[0051] In this step, when the reaction temperature and stirring speed are within the range, if the reaction time is less than 1.0h, the reaction is not thorough, the transition metal oxide / carbon composite microspheres have fewer transition metal oxide particles on the surface, and the morphology of the carbon microspheres cannot be maintained during the preparation of the transition metal oxide / carbon composite microspheres; if the reaction time is greater than 5.0h, the morphology of the transition metal oxide / carbon composite microspheres is significantly different from that of the target product. Therefore, a reaction time of 1.0-5.0h is reasonable, preferably 2.0-4.0h.

[0052] In this step, the purpose of filtering and washing the reactants after cooling to room temperature is to remove unreacted golf ball-like polymer microspheres and inorganic salts containing transition metals. The main purpose of drying the precipitate is to obtain dry transition metal oxide / carbon composite microsphere powder for preparing transition metal oxide / carbon composite microspheres.

[0053] According to the present invention, the transition metal oxide / carbon composite microspheres obtained in this step are observed using a scanning electron microscope sold by Japan's HITACHI company under the trade name scanning electron microscope. The results show that the particle size of the transition metal oxide / carbon composite microspheres ranges from 2 to 6 μm, and the surface of the microspheres themselves is distributed with depressions of varying sizes, similar to the surface of a golf ball, and transition metal oxide particles are distributed on the surface of the microspheres.

[0054] B. Preparation of transition metal oxide / carbon composite microspheres

[0055] The microsphere precursor obtained in step A is placed in a tubular furnace, heated to 600-1000° C. at a gas flow rate of 100-200 mL / min and a heating rate of 2.0-10.0° C. / min under nitrogen protection, and carbonized for 1-4 hours to obtain a black product, which is the transition metal oxide / carbon composite microsphere.

[0056] In this step, the main function of carbonization is to improve the conductivity of carbon materials, form a stable amorphous carbon structure, improve the thermal stability of carbon materials, and transform the adsorbed inorganic salts into transition metal oxides.

[0057] In this step, the main purpose of introducing nitrogen is to prevent the reactants from reacting with air during the carbonization process, thereby destroying the stability of the product, and to prevent the local temperature from being too high.

[0058] When the nitrogen introduction rate, the heating rate and the carbonization time are within the described range, if the carbonization temperature is too low, the carbonization degree of the product is not high; if the carbonization temperature is too high, fewer transition metal oxide particles remain on the surface of the product, resulting in an uneven product morphology; therefore, a carbonization temperature of 600-1000°C is reasonable.

[0059] When the speed of nitrogen introduction, the heating rate and the carbonization temperature are within the range, if the carbonization time is less than 1 hour, the carbonization degree of the obtained product is not high, and the carbonization degree inside the raw material is too small, resulting in reduced energy storage performance; if the carbonization time is greater than 4 hours, there are fewer transition metal oxide particles remaining on the surface of the product, resulting in uncontrollable product morphology. Therefore, a carbonization time of 1-4 hours is reasonable.

[0060] When the speed of nitrogen introduction, carbonization temperature and carbonization time are within the range, if the heating rate is less than 2.0°C / min, the carbonization time is too long and the pore structure of the product basically does not change in the later stage; if the heating rate is greater than 10°C / min, the transition metal oxide particles on the surface of the product will be greatly reduced and the product morphology will be destroyed. Therefore, a heating rate of 2-10°C / min is reasonable.

[0061] When the carbonization temperature, heating rate and carbonization time are within the range, if the nitrogen introduction rate is less than 100 mL / min or greater than 200 mL / min, the energy storage performance of the product is reduced. Therefore, it is reasonable to introduce nitrogen at a rate of 100-200 mL / min.

[0062] The invention also relates to transition metal oxide / carbon composite microspheres prepared by the preparation method.

[0063] The transition metal oxide / carbon composite microspheres prepared by the above-mentioned preparation method were tested using the above-mentioned scanning electron microscope and the energy spectrometer sold by Thermo Company under the trade name of energy dispersive X-ray spectrometer. The results showed that the transition metal oxide / carbon composite microspheres contained three basic elements of C, N, and O, and also contained one or more of four elements of Mn, Co, Fe, and Ni. The composite microspheres had a particle size of 2 to 6 μm, a concave surface and were loaded with different transition metal oxide particles, with a specific surface area of ​​208 to 252 m 2 g -1 , the average pore diameter is 2.1824~2.2453nm.

[0064] The present invention also relates to the application of the transition metal oxide / carbon composite microspheres in preparing supercapacitor electrode materials.

[0065] According to the present invention, the preparation method of the supercapacitor electrode material is as follows: 5 to 20 mg of transition metal oxide / carbon composite microspheres as active materials are mixed with a binder and N-methylpyrrolidone in a weight ratio of 9:1:20 to form a uniform slurry, and the slurry is evenly coated on a 1 cm 2 The working electrode is pressed onto the nickel foam after drying; the working electrode, the platinum electrode and the mercury / mercury oxide electrode form a three-electrode system. The electrolyte is 4-6 mol / L KOH and the current density is 0.5-10 A·g -1 The mass specific capacitance is 387~214F·g -1 When the current density is 10A·g -1 The capacitance retention rate after 10,000 charge and discharge cycles is 90-96%.

[0066] The present invention uses an electrochemical workstation sold by Swiss Metrology under the trade name Autolab PGSTAT302N to test cyclic voltammetry (CV), constant current charge-discharge curve (GCD) and cycle stability curve under normal temperature. According to the document Yulin Zhang, et al, title "Evaluation of electrochemical performance ofsupercapacitors from equivalent circuits through cyclic voltammetry andgalvanostatic charge / discharge, (Journal of Energy Storage, 86 (2024): 111122.)", the mass specific capacitance of the carbon material and the capacitance retention rate after 10,000 cycles are calculated, and the results are shown in the embodiment section.

[0067] The present invention will be better understood through the following examples, but the present invention is not limited to these examples.

[0068] The following examples use the following analytical methods to analyze the materials: scanning electron microscopy and transmission electron microscopy are used for microscopic morphology analysis, specific surface area analyzer and nitrogen adsorption and desorption method (literature: Journal of Energy Storage, 85 (2024): 111160.) are used to test and analyze the pore structure of transition metal oxide / carbon composite microspheres, and energy dispersive X-ray spectrometer is used to test the elemental composition of the material.

[0069] Embodiment 1:

[0070] A. Preparation of microsphere precursor

[0071] Putting golf ball-like polymer microspheres poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) and potassium permanganate into an ethanol-water solution with a concentration of 80% by weight, dissolving and dispersing by ultrasonication to obtain a mixed solution I;

[0072] The mass ratio of the potassium permanganate, golf ball-shaped polymer microspheres and ethanol-water solution is 0.002:0.008:1;

[0073] The mixed solution I was transferred to a three-necked flask and reacted at room temperature and a stirring speed of 300 rpm for 1 h. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor.

[0074] B. Preparation of transition metal oxide / carbon composite microspheres

[0075] The microsphere precursor obtained in step A was placed in a tube furnace, heated to 1000°C under nitrogen protection at a gas flow rate of 100 mL / min and a heating rate of 2.0°C / min, and carbonized for 1 hour to obtain a black product, which is the transition metal oxide / carbon composite microsphere. Table 1: Energy dispersive X-ray spectrometer test results of the transition metal oxide / carbon composite microspheres prepared in this example.

[0076] Table 1. Energy dispersive X-ray spectrometer test results

[0077] Element Family Atomic Fraction(%) Mass Fraction(%) C K 67.22 54.75 N K 15.07 14.31 O K 13.27 14.40 Mn K 4.44 16.54

[0078] According to the energy dispersive X-ray spectrometer, scanning electron microscope ( Figure 1 -a) Nitrogen adsorption and desorption test ( Figure 1 -b) and X-ray diffraction ( Figure 1-c) The test results confirmed that it is composed of C, N, O and Mn elements in a weight ratio of 54.75:14.31:14.40:16.54. It is golf ball-shaped in the macro sense, with depressions and manganese oxide particles on the surface. In the micro sense, it is composed of micropores with an average pore size of 2.2453nm and a specific surface area of ​​208m 2 ·g -1 The XRD results showed the characteristic peaks of manganese oxide, indicating that the prepared transition metal oxide / carbon composite microspheres were manganese oxide / carbon composite microspheres.

[0079] Embodiment 2:

[0080] A. Preparation of microsphere precursor

[0081] Putting golf ball-like polymer microspheres poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) and cobalt chloride into an ethanol-water solution with a concentration of 20% by weight, dissolving and dispersing by ultrasonication to obtain a mixed solution I;

[0082] The mass ratio of the cobalt chloride, golf ball-shaped polymer microspheres and ethanol-water solution is 0.02:0.08:1;

[0083] The mixed solution I was transferred to a three-necked flask and reacted for 5 h at room temperature and a stirring speed of 800 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor.

[0084] B. Preparation of transition metal oxide / carbon composite microspheres

[0085] The microsphere precursor obtained in step A was placed in a tube furnace, heated to 600°C under nitrogen protection at a gas flow rate of 200 mL / min and a heating rate of 10.0°C / min, and carbonized for 4 hours to obtain a black product, which is the transition metal oxide / carbon composite microsphere. The scanning electron microscope image thereof is shown in Figure 2 Table 2: Energy dispersive X-ray spectrometer test results of the transition metal oxide / carbon composite microspheres prepared in this example.

[0086] Table 2. Energy dispersive X-ray spectrometer test results

[0087] Element Family Atomic Fraction(%) Mass Fraction(%) C K 66.42 50.02 N K 11.53 10.13 O K 15.47 15.53 Co K 6.58 24.32

[0088] According to the results of energy dispersive X-ray spectrometer, scanning electron microscope, nitrogen adsorption and desorption test and X-ray diffraction test, it is composed of C, N, O and Co elements in a weight ratio of 50.02:10.13:15.53:24.32, with depressions and cobalt oxide particles on the surface. Microscopically, it is composed of micropores with an average pore size of 2.1824nm and a specific surface area of ​​252m2 ·g -1 .

[0089] Embodiment 3:

[0090] A. Preparation of microsphere precursor

[0091] Putting golf ball-like polymer microspheres poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile), manganese chloride tetrahydrate and cobalt chloride hexahydrate into an ethanol-water solution with a concentration of 40% by weight, dissolving and dispersing by ultrasonication to obtain a mixed solution I;

[0092] The mass ratio of the manganese chloride tetrahydrate, cobalt chloride hexahydrate, golf ball-shaped polymer microspheres and ethanol-water solution is 0.005:0.005:0.02:1;

[0093] The mixed solution I was transferred to a three-necked flask and reacted for 3 h at room temperature and a stirring speed of 500 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor.

[0094] B. Preparation of transition metal oxide / carbon composite microspheres

[0095] The microsphere precursor obtained in step A was placed in a tube furnace, heated to 900°C under nitrogen protection at a gas flow rate of 120 mL / min and a heating rate of 5.0°C / min, and carbonized for 2 hours to obtain a black product, which is the transition metal oxide / carbon composite microsphere. The scanning electron microscope image thereof is shown in Figure 3 .

[0096] Embodiment 4:

[0097] A. Preparation of microsphere precursor

[0098] Putting golf ball-like polymer microspheres poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile) and manganese sulfate, cobalt sulfate, and nickel sulfate into a 60% by weight ethanol-water solution, dissolving and dispersing by ultrasonication, to obtain a mixed solution I;

[0099] The mass ratio of the manganese sulfate, cobalt sulfate, nickel sulfate, golf ball-shaped polymer microspheres and ethanol-water solution is 0.003:0.003:0.005:0.06:1;

[0100] The mixed solution I was transferred to a three-necked flask and reacted for 4 h at room temperature and a stirring speed of 600 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor.

[0101] B. Preparation of transition metal oxide / carbon composite microspheres

[0102] The microsphere precursor obtained in step A was placed in a tube furnace, heated to 800°C at a heating rate of 8.0°C / min under the protection of 110 mL / min nitrogen, and carbonized for 3 hours to obtain a black product, which is the transition metal oxide / carbon composite microsphere. The scanning electron microscope image thereof is shown in Figure 4 .

[0103] Example 5

[0104] A. Preparation of microsphere precursor

[0105] Putting golf ball-like polymer microspheres poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile), manganese chloride tetrahydrate and cobalt chloride hexahydrate into an ethanol-water solution with a concentration of 30% by weight, and dissolving and dispersing by ultrasonication to obtain a mixed solution I;

[0106] The mass ratio of manganese chloride tetrahydrate, cobalt chloride hexahydrate, ferric chloride hexahydrate, nickel chloride hexahydrate, golf ball-shaped polymer microspheres and ethanol-water solution is 0.002:0.002:0.0015:0.0015:0.05:1;

[0107] The mixed solution I was transferred to a three-necked flask and reacted for 4 h at room temperature and a stirring speed of 800 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor.

[0108] B. Preparation of transition metal oxide / carbon composite microspheres

[0109] The microsphere precursor obtained in step A was placed in a tube furnace, heated to 850°C under nitrogen protection at a gas flow rate of 100 mL / min and a heating rate of 6.0°C / min, and carbonized for 2 hours to obtain a black product, which is the transition metal oxide / carbon composite microsphere. The scanning electron microscope image thereof is shown in Figure 5 .

[0110] The golf ball-like polymer microspheres, inorganic salts containing transition metals, and alcohol aqueous solutions used in the above embodiments may also be other types of substances within the aforementioned limited range, and they can all achieve similar technical effects as embodiments 1-4, and will not be described one by one here.

[0111] Application Example 1:

[0112] The implementation of the application is as follows:

[0113] The transition metal oxide / carbon composite microspheres prepared in Example 1 were uniformly filled in a 1 cm 3The nickel foam vacancy was filled and then pressed into a working electrode; the working electrode, platinum electrode, mercury / mercury oxide electrode and 4 mol / L KOH electrolyte formed a three-electrode system. The CV, GCD and cycle stability curves were tested at room temperature using an electrochemical workstation sold by Swiss Metrohm under the trade name Autolab PGSTAT 302N. The mass specific capacitance and cycle stability of the transition metal oxide / carbon composite microspheres were calculated according to the method described in this specification, and the results are listed in the attached Figure 5 . Figure 5 It can be seen that the transition metal oxide / carbon composite microspheres have a current density of 0.5A·g -1 , 1A·g -1 , 3A g -1 , 5A g -1 , 10A·g -1 The mass specific capacitance is 330F·g -1 、290F·g -1 , 270F·g -1 , 258F·g -1 , 214F·g -1 When the current density is 10A·g -1 The capacitance retention rate after 10,000 charge and discharge cycles is 92%.

[0114] Application Example 2:

[0115] The implementation of the application is as follows:

[0116] The transition metal oxide / carbon composite microspheres prepared in Example 4 were uniformly filled in a 1 cm 3 The nickel foam gap is filled and then pressed into a working electrode; the working electrode, platinum electrode, mercury / mercury oxide electrode and 6 mol / L KOH electrolyte form a three-electrode system. The CV, GCD and cycle stability curves are tested at room temperature using an electrochemical workstation sold by Swiss Metrohm under the trade name Autolab PGSTAT 302N. The mass specific capacitance and cycle stability of the transition metal oxide / carbon composite microspheres are calculated according to the method described in this specification. The transition metal oxide / carbon composite microspheres are -1 , 1A·g -1 , 3A g -1 , 5A g -1 , 10A·g -1 The mass specific capacitance is 387F·g -1 、350F·g -1 、300F·g -1 , 288F·g -1 , 226F·g -1 When the current density is 10A·g-1 The capacitance retention rate after 10,000 charge and discharge cycles is 96%.

[0117] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A transition metal oxide / carbon composite microsphere, characterized in that: It uses carbon microspheres as carriers, and the surface of the carbon microspheres is concave and evenly distributed with one or more transition metal oxide particles; The carbon microspheres are formed by carbonizing golf ball-shaped polymer microspheres and have wrinkles on the surface; The transition metal oxide particles are formed by adsorbing inorganic salts containing transition metals on the surface of golf ball-shaped polymer microspheres and then carbonizing and oxidizing at high temperature; The transition metal oxide / carbon composite microspheres contain three elements of C, N, and O, and at least one of four elements of Mn, Co, Fe, and Ni; The inorganic salt containing transition metal is selected from potassium permanganate, cobalt chloride, manganese chloride tetrahydrate, cobalt chloride hexahydrate, ferric chloride hexahydrate, nickel chloride hexahydrate, manganese sulfate, cobalt sulfate, ferric sulfate or nickel sulfate; The preparation method of the transition metal oxide / carbon composite microspheres comprises the following steps: A. Preparation of microsphere precursor Putting golf ball-shaped polymer microspheres and one or more inorganic salts containing transition metals into an alcohol aqueous solution with a concentration of 20 to 80% by weight, dissolving and dispersing by ultrasonication to obtain a mixed solution I; The mass ratio of the inorganic salt containing transition metal, golf ball-shaped polymer microspheres and alcohol aqueous solution is 0.002-0.02:0.008-0.08:1; The mixed solution I was transferred to a three-necked flask, and reacted for 1-5 hours at room temperature and a stirring speed of 300-800 rpm. Finally, the reactant was cooled to room temperature, the product was filtered out, and then dried to obtain a microsphere precursor; B. Preparation of transition metal oxide / carbon composite microspheres The microsphere precursor obtained in step A is placed in a tube furnace, and heated to 600-1000° C. at a gas flow rate of 100-200 mL / min and a heating rate of 2.0-10.0° C. / min under argon protection for carbonization for 1-4 hours to obtain black product transition metal oxide / carbon composite microspheres.

2. The transition metal oxide / carbon composite microspheres according to claim 1, characterized in that: The particle size of the carbon microspheres is 2-6 μm, and the specific surface area is 208-252 m 2 ·g -1 , the average pore diameter is 2.1824~2.2453 nm.

3. The transition metal oxide / carbon composite microspheres according to claim 1, characterized in that: The golf ball-like polymer microspheres are selected from poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl phthalate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl isophthalate-co-cyclohexyl methacrylate-co-acrylonitrile) or poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile).

4. The transition metal oxide / carbon composite microspheres according to claim 3, characterized in that: The golf ball-like polymer microspheres are selected from poly(diallyl phthalate-co-methyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl terephthalate-co-glycidyl methacrylate-co-acrylonitrile) copolymer microspheres, poly(diallyl maleate-co-cyclohexyl methacrylate-co-acrylonitrile) copolymer microspheres or poly(diallyl maleate-co-ethyl methacrylate-co-acrylonitrile).

5. The transition metal oxide / carbon composite microspheres according to claim 1, characterized in that: The alcohol aqueous solution is a methanol aqueous solution, an ethanol aqueous solution, an isopropanol aqueous solution, a n-propanol aqueous solution or a tert-butanol aqueous solution.

6. Use of the transition metal oxide / carbon composite microspheres according to any one of claims 1 to 5 in preparing supercapacitor electrode materials.

Citation Information

Patent Citations

  • Metal oxide composite carbon sphere and preparation method thereof

    CN109437322A

  • Golf-like porous carbon material and preparation method and application thereof

    CN117577453A